2022
DOI: 10.14582/duzgef.2022.189
|View full text |Cite
|
Sign up to set email alerts
|

Üstün Yetenekli Öğrencilerin Eğitiminde Farklılaştırma ve Zenginleştirme Uygulamalarına İlişkin Yapılan Lisansüstü Tezlerin İncelenmesi

Abstract: Üstün yetenekli öğrenciler, özel eğitim kapsamında yer almakta, bilişsel gelişimleri akranlarından ileride olduğu için eğitimlerinde farklı uygulamalara gereksinim duymaktadır. Bu bağlamda farklılaştırma ve zenginleştirme uygulamaları üstün yetenekli öğrencilerin eğitimlerinde yaygın olarak kullanılmaktadır. Özellikle son yıllarda Türkiye’de bu konuda yapılan araştırma ve tezlerin sayısında bir artış görülmektedir. Ancak konu ile ilgili yapılan lisansüstü tezlerin ayrıntılı şekilde incelendiği bir araştırmaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The findings of the study indicate that out of the 31 theses prepared in Turkey on differentiated instruction for gifted students, 25 are doctoral theses and 6 are master's theses. Kaya et al (2022) found in their research that out of the 31 theses they examined, 22 were doctoral theses and 9 were master's theses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the study indicate that out of the 31 theses prepared in Turkey on differentiated instruction for gifted students, 25 are doctoral theses and 6 are master's theses. Kaya et al (2022) found in their research that out of the 31 theses they examined, 22 were doctoral theses and 9 were master's theses.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are no studies on secondary level courses such as history, geography, literature, physics and biology. Kaya et al (2022) stated in their study that thesis studies on differentiated instruction were mostly conducted in the fields of mathematics, geometry and science, while fewer studies were conducted in the fields of social studies, Turkish, English and fine arts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects on the affective and cognitive areas of gifted students and the results that activity/module/program/scale studies developed for gifted individuals are applicable are also quite high. The training provided for gifted individuals is not sufficient (Çelik Şahin, 2021); considering that there is no special education program (Kaya, Mertol, Turhan, Araz and Uçar, 2022) due to the fact that the education of gifted students is based on recent times in Türkiye, it is a necessity as a result of developing an activity/program/scale for gifted individuals.…”
Section: Discussionmentioning
confidence: 99%
“…When the suggestions made for the gifted education program for the decision makers are examined, the majority of the suggestions are to add the modules and activities developed in the graduate theses to the curriculum. Another suggestion is to create a special education program for gifted students, as emphasized by many researchers in the literature (Çelik Şahin, 2021;Kaya, Mertol, Turhan, Araz and Uçar, 2022). In addition, among the suggestions made for the curriculum, "Increasing innovative innovation project practices", "Separate procedures in university exams", "Organizing a single and separate educational activity", "creating educational standards" were found to be original by the researchers.…”
Section: Discussionmentioning
confidence: 99%